Narratives about the Macroeconomy - Peter Andre; Ingar Haaland; Christopher Roth; Johannes Wohlfart (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2021)
We provide evidence on narratives about the macroeconomy — the stories people tell to explain macroeconomic phenomena — in the context of a historic surge in inflation. We measure economic narratives in open-ended survey responses and represent them as Directed Acyclic Graphs. We apply this approach in surveys with more than 8,000 US households and 100 academic experts. We document three main findings. First, compared to experts, households' narratives are coarser, focus less on the demand side, and are more likely to feature politically-loaded explanations. Second, households' narratives strongly shape their inflation expectations, which we demonstrate with descriptive survey data and a series of experiments. Third, an experiment varying news consumption shows that the media is an important source of narratives. Our findings demonstrate the relevance of narratives for understanding macroeconomic expectation formation.
Keywords: D83; D84; E31; E52; E71; 330; Narratives; Expectation Formation; Causal Reasoning; Inflation; Media; Attention